Association between Birth Characteristics and Cardiovascular Autonomic Function at Mid-Life - Perkiömäki, Nelli; Auvinen, Juha; Tulppo, Mikko P.; Hautala, Arto J.; Perkiömäki, Juha; Karhunen, Ville; Keinänen-Kiukaanniemi, Sirkka; Puukka, Katri; Ruokonen, Aimo; Järvelin, Marjo-Riitta; Huikuri, Heikki V.; Kiviniemi, Antti M. (PloS one, 2016)
Low birth weight is associated with an increased risk of cardiovascular diseases in adulthood. As abnormal cardiac autonomic function is a common feature in cardiovascular diseases, we tested the hypothesis that low birth weight may also be associated with poorer cardiac autonomic function in middle-aged subjects. At the age of 46, the subjects of the Northern Finland Birth Cohort 1966 were invited to examinations including questionnaires about health status and life style and measurement of vagally-mediated heart rate variability (rMSSD) from R-R intervals (RRi) and spontaneous baroreflex sensitivity (BRS) in both seated and standing positions. Maternal parameters had been collected in 1965-1966 since the 16th gestational week and birth variables immediately after delivery. For rMSSD, 1,799 men and 2,279 women without cardiorespiratory diseases and diabetes were included and 902 men and 1,020 women for BRS. The analyses were adjusted for maternal (age, anthropometry, socioeconomics, parity, gestational smoking) and adult variables (life style, anthropometry, blood pressure, glycemic and lipid status) potentially confounding the relationship between birth weight and autonomic function. In men, birth weight correlated negatively with seated (r = -0.058, p = 0.014) and standing rMSSD (r = -0.090, p<0.001), as well as with standing BRS (r = -0.092, p = 0.006). These observations were verified using relevant birth weight categories (<2,500 g; 2,500-3,999 g; ≥4,000 g). In women, birth weight was positively correlated with seated BRS (r = 0.081, p = 0.010), but none of the other measures of cardiovascular autonomic function. These correlations remained significant after adjustment for potential confounders (p<0.05 for all). In men, higher birth weight was independently associated with poorer cardiac autonomic function at mid-life. Same association was not observed in women. Our findings suggest that higher, not lower, birth weight in males may contribute to less favourable cardiovascular autonomic regulation and potentially to an elevated cardiovascular risk in later life.